Effects of husk charcoal and watering on the biochemical and physiological properties of coix millet (Coix lacryma jobi L.) during vegetative phase - Fadillatunnisa Fadillatunnisa; Didik Indradewa; Eka Tarwaca Susila Putra (Jurnal Ilmu Pertanian, 2023)
Continuous climate change increases the number of droughts in some areas, thereby affecting agricultural production. Cultivation of coix millet (Jali plant in Indonesian) is profitable because of its high adaptability to drought stress, and its seeds have the potential to be used as food due to their benefits for body health. The application of organic matter, namely husk charcoal, was chosen to increase agricultural production under drought stress. Therefore, this study aimed to determine the effects of husk charcoal on the biochemical and physiological properties of coix millet during vegetative phase under drought stress and to determine the longest watering interval the plant can tolerate. Research was arranged in a split-plot design with three replications. The main plot consisted of three watering intervals (every two, four, and six days). The sub-plots consisted of three doses of husk charcoal, namely 0 g polybag⁻¹ (0 tons ha⁻¹), 32 g polybag⁻¹ (10 tons ha⁻¹), and 64 g polybag⁻¹ (20 tons ha⁻¹). The data were analyzed using analysis of variance (ANOVA) and tested using Duncan's Multiple Distance Test (DMRT) at a significant level of 5%. The results showed that husk charcoal could increase the chlorophyll content in plants experiencing drought stress. The longest watering interval that could be tolerated by coix millet given husk charcoal at the optimal dose (64 g polybag⁻¹) was once every four days.